A population of very young brown dwarfs and free-floating planets in Orion - Lucas, P; Roche, P (2000)
We describe the results of a very deep imaging survey of the Trapezium cluster in the IJH bands, using the UKIRT high-resolution camera UFTI. Approximately 32 per cent of the 515 point sources detected are brown dwarf candidates, including several free-floating objects with masses below the deuterium-burning (planetary) threshold at 0.013 M⊙, which are detectable because of their extreme youth. We have confidence that almost all the sources detected are cluster members, since foreground contamination is minimal in the 33-arcmin2 area surveyed, and the dense backdrop of OMC-1 obscures all background stars at these wavelengths. Extinction is calculated from the (J - H) colours, permitting accurate luminosity estimates, and temperatures are derived from the dereddened (I - J) colours. There is some evidence for a cut-off in the luminosity function below the level corresponding to several Jupiter masses, which may represent the bottom end of the initial mass function. Since star formation is complete in the Trapezium, this limit could have wide significance, if confirmed. However, it could well be an effect of the dispersal of the molecular cloud by the central O-type stars, a process for which the time-scale will vary between star formation regions.